2015
DOI: 10.1007/s11101-015-9418-0
|View full text |Cite
|
Sign up to set email alerts
|

Alkamides: a critical reconsideration of a multifunctional class of unsaturated fatty acid amides

Abstract: Alkamides are natural products formed by connecting straight-chain, mostly unsaturated, aliphatic acids with various amines by an amide linkage. More than 300 derivatives are known from eight plant families consisting of various combinations of 200 acids with 23 amines. Apart from a few saturated derivatives alkamides with unsaturated acid parts are grouped into compounds with purely olefinic patterns and those with olefinic and acetylenic linkages. Derived from C 18 oleic acid the acid parts are modified eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 241 publications
(256 reference statements)
2
46
0
2
Order By: Relevance
“…Again, exception for piperovatine that has a methoxy as substituent. This chemical pattern is in agreement with those from literature records for N-akylamides from Piper species (Parmar et al 1997, Boonen et al 2012, Greger 2016. Besides, some other amides isolated from the genus Ottonia, such as piperlonguminine, corcovadine and isocorcovadine fit in this profile (Costa and Mors 1981).…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Again, exception for piperovatine that has a methoxy as substituent. This chemical pattern is in agreement with those from literature records for N-akylamides from Piper species (Parmar et al 1997, Boonen et al 2012, Greger 2016. Besides, some other amides isolated from the genus Ottonia, such as piperlonguminine, corcovadine and isocorcovadine fit in this profile (Costa and Mors 1981).…”
Section: Introductionsupporting
confidence: 91%
“…Only pipercallosidine of all three isolated amides could be assayed due to the affordable amount. The characterized metabolites found in O. anisum root extract were in agreement with those from literature data for Piperaceae species (Parmar et al 1997, Ahmad et al 2012, Greger 2016) but just piperovatine and the amide (2E, 4E)-N-isobutyl-9-piperonyl-nona-2,4-dienoic have been described for O. anisum (Giesbrecht et al 1981). Species of the genus Piper and Ottonia have been related as natural sources for alkylamides.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although alkylamide suppression of cytokine production has been described previously, the mechanism by which alkylamide-containing medicinal plants mediate their effects remains controversial (Boonen et al, 2012; Greger, 2016). In this report, we evaluated the effects of the alkylamide A15 on mast cell degranulation and calcium influx and found that it inhibited degranulation from RBL-2H3 cells and BMMCs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually used as a characteristic spice with unique tingling taste in the food industry, and is also used to treat toothache, ascariasis, gastralgia, dyspepsia, eczema, and so on, as a traditional Chinese medicine (Ahua et al., 2007; Tewary, Bhardwaj, & Shanker, 2005; Yang, Su, Li, Zhang, & Sun, 2008). In recent years, Z. bungeanum has been considered to be an appealing material for the research of bioactive compounds, including acid amide, volatile oil, alkaloids, and phenolic compounds (Greger, 2016; Wang et al., 2010; Xiong, Shi, & Mizuno, 1995; Yang, Li, Tan, & Jiang, 2013; Zhang et al., 2017). Particularly, the phenolic compounds of Z. bungeanum exhibit outstanding pharmacological activities, such as antioxidant, antibacterial, antitumor, etc.…”
Section: Introductionmentioning
confidence: 99%